Determination of Warehouse Performance Measurement Indicators at PT Pos Logistik Indonesia with The Balanced Scorecard Method - Adji Candra Kurniawan; Ismi Nur Octaviani Harsono; Nanda Ruswandi (Majalah Ilmiah Bijak, 2023)
PT Pos Logistik Indonesia is a subsidiary of PT Pos Indonesia. This research focuses on PT Pos Logistik Indonesia Unilever Cakung warehouse, which later researchers will determine warehouse performance indicators using the Balanced Scorecard method. In the current conditions, the company only measures performance on employees and internal business activities and only focuses on one financial indicator. Therefore, it is necessary to have indicators that cover all aspects in realizing the vision and mission of the company. This study aims to compile appropriate indicators and propose additional indicators that need to be applied by companies for each perspective on the Balanced Scorecard method and determine priority weights for each perspective. The thing to do is to solve it by determining a strategy that is in accordance with the company's vision and mission that is adjusted to the company's activities, then by being able to determine suitable performance indicators to be implemented in the company PT Pos Logistik Indonesia. Then you can weight the interests of each performance indicator from four perspectives to find out which indicators are the most important to implement and prioritize. After calculating using Super Decision software, it is found that the customer perspective has a priority weight value of 0.333, the finance perspective has a priority weight value of 0.298, the internal process perspective has a priority weight value of 0.257 and the learning and growth perspective has a priority weight value of 0.113. The highest weight is on the customer perspective so that this perspective is more important than other perspectives